Selectivity Studies On Malaysian Trawls - Haji Mohamed, Mohd Ibrahim (1987)
A covered cod-end experiment was conducted employing 70 hauls of fish and shrimp trawls in the South China Sea and the Malacca Straits to determine the selectivity pattern of Malaysian trawls . This study was conducted in order to alleviate the intensive fishing effort on the fishery stocks especially towards the juveniles of commercially important species . A mathematical model was developed to predict the selection curve based on the standard length and maximum body depth of fish and shrimp species retained by the net .collection in a selectivity experiment is now simplified to obtaining the two parameters from fish or shrimp sampled from any catch . Results of the study revealed that the 25 mm cod-end fish trawl retained 98 . 2 percent as compared to the 51 mm cod-end which retained 56 . 1 percent of the catch . With the shrimp trawl , the 25 mm cod-end retained 9 2 . 6 percent while the 38 mm cod-end retained 5 1 . 35 percent of the catch .